Optimization of blood pressure control, organ protection and metabolic disorders using a fixed-dose combination of lisinopril+amlodipine+rosuvastatin in hypertensive patients after COVID-19 - S. V. Nedogoda; A. A. Ledyaeva; E. V. Chumachek; V. V. Tsoma; A. S. Salasyuk; V. O. Lutova; E. A. Popova; D. S. Vlasov; O. I. Bychkova; V. A. Labaznikova; K. S. Evdokimov (Российский кардиологический журнал)
Aim. To evaluate the potential of a fixed-dose combination of lisinopril+amlodipine+rosuvastatin (Equamer®) in achieving additional vascular protection in patients with hypertension and high pulse wave velocity (PWV) after severe and very severe coronavirus disease 2019 (COVID-19), complicated by bilateral multisegmental viral pneumonia, with the use of biological therapy, who had not previously received combination antihypertensive therapy.Material and methods. This 12-week open-label observational study included 30 patients with or without antihypertensive therapy. The patients underwent 24-hour blood pressure monitoring, applanation tonometry (determination of the augmentation index (AI) and central blood pressure (CBP)), PWV measurement, blood laboratory tests (lipid profile, fasting glucose, C-reactive protein, complete blood count, ferritin, fibrinogen, D-dimer, alanine aminotransferase, aspartate aminotransferase, creatinine, uric acid) before and after switch to a fixed-dose combination of lisinopril+amlodipine+rosuvastatin.Results. At baseline, the patients had an increase in office blood pressure (BP) up to 152,6/89,1 mm Hg. After prescribing a fixed-dose combination of lisinopril+amlodipine+rosuvastatin, there was a decrease in systolic blood pressure (SBP) by 15,8% and diastolic blood pressure (DBP) by 12,2%. According to 24-hour blood pressure monitoring, the decrease in SBP was 15%, DBP — by 9%, PWV — by 23,8%, AI — by 9%, CBP — by 12,4% (p<0,05 for all compared to baseline values). Vascular age (VA) was initially increased to 41,9 years with a chronological age of 35,03 years. After the end of therapy, there was a significant decrease in VA to 36,5 years, low-density lipoproteins by 46,8%, triglycerides by 16,8% and an increase in high-density lipoproteins by 10,7% (p<0,05 for all compared to baseline values). In addition, the levels of C-reactive protein, fibrinogen, D-dimer, glucose, and uric acid significantly decreased.Conclusion. The fixed-dosed combination of lisinopril+amlodipine+rosuvastatin provides better blood pressure control, improved vascular elasticity parameters (AI, PWV, CBP, decrease in VA), and also improves lipid and carbohydrate metabolism, reduces inflammation in patients with hypertension and hyperlipidemia after severe COVID-19.